The invisible man - Vogel, Malvina G.; Wells, H. G. (Herbert George), 1866-1946. (New York, N.Y. : Baronet Books, 1995)
An adaptation of Wells' story about a scientist who discovers how to make his body become invisible, but, when he can't make himself visible again, becomes violently insane.
4.8
5-8
5-8
Wilson's Senior High School
Wilson's Fiction
980
Keywords: Scientists -- Fiction; Science fiction; Scientists -- Fiction; Science fiction